F(x, y) = 1 - e^-x - e^-y + e^(-x-y), x>0, y>0. I am supposed to find P(X + Y > 3).
I am messing up somewhere along the way, and I don't know where. What I'm doing is:
1. Finding f(x, y) = F_xy(x, y), which comes to e^-x * e^-y.
2. Setting P(X + Y > 3) = 1 - P(X + Y <= 3).
3. Setting P(X + Y <= 3) =
4. Solving to get 4e^-3. But the back of the book says the answer is (e^-2 - e^-3)^2.
I really have no clue what I'm doing wrong. The book is very unclear with its examples; it only gives rectangular regions.
Please help. I really need to get this done. And I am still awaiting help on this problem, which I am no closer to solving.